Kiss of frost ebook - Estep, Jennifer (Mythos Academy, 2011)
A high school warrior-in-training gets lessons in surviving a mysterious assassin in the New York Times bestselling author's YA urban fantasy novel. I'm Gwen Frost, a second-year warrior-in-training at Mythos Academy, and I have no idea how I'm going to survive the rest of the semester. One day, I'm getting schooled in swordplay by the guy who broke my heart—the drop-dead gorgeous Spartan Logan Quinn who slays me every time. Then, an invisible archer in the Library of Antiquities decides to use me for target practice. And now, I find out that someone at the academy is really a Reaper bad guy who wants me dead. Now, with Logan's help, I'll have to learn to live by the sword—or die trying.